2018
DOI: 10.7202/1047049ar
|View full text |Cite
|
Sign up to set email alerts
|

Une porphyrine comme photosensibilisant des eaux d'irrigation, photostabilité et efficacité

Abstract: Le processus de photosensibilisation (phototraitement) de l'eau suscite beaucoup d'intérêt, car il implique trois composants qui sont individuellement inoffensifs pour le milieu biologique, à savoir le photosensibilisant, la lumière et l'oxygène moléculaire. La photostabilité de la porphyrine tétra-méso-cationique (T4MPyP) dans l'eau usée et l’efficacité du phototraitement dépend de la concentration du photosensibilisant, de la qualité de l'eau (contaminants organiques, turbidité, pH, taux d'oxygène dissous et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In Tunisia, the extensive system under which the camel herds are conducted is characterized by a diet based on natural resources (Moslam and Megdich, 1989;Moslah et al, 2004;Letaief and Bedhiaf-Romdhani, 2022). The breeding practices are almost only traditional due to feeding constraints (Ould Ahmed et al, 2009;Jemli et al, 2018). In another study, Tardif et al (2014) reported that well-trained keepers manage camel rearing in Najjar / Uluslararası Tarım Araştırmalarında Yenilikçi Yaklaşımlar Dergisi / International Journal of Innovative Approaches in Agricultural Research, 2024, Vol.…”
Section: Characterization Of Camel Breedingmentioning
confidence: 99%
“…In Tunisia, the extensive system under which the camel herds are conducted is characterized by a diet based on natural resources (Moslam and Megdich, 1989;Moslah et al, 2004;Letaief and Bedhiaf-Romdhani, 2022). The breeding practices are almost only traditional due to feeding constraints (Ould Ahmed et al, 2009;Jemli et al, 2018). In another study, Tardif et al (2014) reported that well-trained keepers manage camel rearing in Najjar / Uluslararası Tarım Araştırmalarında Yenilikçi Yaklaşımlar Dergisi / International Journal of Innovative Approaches in Agricultural Research, 2024, Vol.…”
Section: Characterization Of Camel Breedingmentioning
confidence: 99%